Safety and efficacy of Bacillus licheniformis DSM 32457 as a silage additive for all animal species. (8th August 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on Bacillus licheniformis DSM 32457 as a silage additive for all animal species. Bacillus licheniformis DSM 32457 is presumed safe for the target species, consumers of products from animals fed treated silage and the environment. In the absence of data, the FEEDAP Panel cannot conclude on the potential of the additive to be a skin/eye irritant or skin sensitiser. Given the proteinaceous nature of the active agent, the additive should be considered a potential respiratory sensitiser. In the absence of appropriate data, the FEEDAP Panel cannot conclude on the efficacy of Bacillus licheniformis DSM 32457 as a silage additive.